2023
DOI: 10.3390/nu15030547
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Administration in Chronic Kidney Disease

Abstract: Awareness of the clinical relevance of magnesium in medicine has increased over the last years, especially for people with chronic kidney disease (CKD), due to magnesium’s role in vascular calcification and mineral metabolism. The inverse association between serum magnesium and clinically relevant, adverse outcomes is well-established in people with CKD. Subsequent intervention studies have focused on the effect of magnesium administration, mainly in relation to cardiovascular diseases, mineral bone metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 104 publications
1
2
0
Order By: Relevance
“…In contrast, our study only found a positive correlation between serum K and CKD, which may be attributed to disparities in study populations, regions, and statistical methods. Prior research has consistently shown that serum Mg concentration is lower in CKD patients compared to controls and is negatively correlated with CKD development, consistent with the findings of Vermeulen and Vervloet ( 20 ). As an essential trace element, the positive influence of Se supplementation on CKD pathogenesis reaffirms our results of this study ( 21 23 ).…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, our study only found a positive correlation between serum K and CKD, which may be attributed to disparities in study populations, regions, and statistical methods. Prior research has consistently shown that serum Mg concentration is lower in CKD patients compared to controls and is negatively correlated with CKD development, consistent with the findings of Vermeulen and Vervloet ( 20 ). As an essential trace element, the positive influence of Se supplementation on CKD pathogenesis reaffirms our results of this study ( 21 23 ).…”
Section: Discussionsupporting
confidence: 85%
“…Approximately 50-60% of magnesium is sequestered in the bone as hydroxyapatite crystal 7) . Only a small fraction of magnesium is stored in the extracellular compartment, approximately 60% of which exists in the biologically active, free form 8) . The normal serum magnesium concentration is 1.7-2.4 mg/dL 6) .…”
Section: Discussionmentioning
confidence: 99%
“…Pada CKD, ginjal kehilangan kemampuannya untuk mengeluarkan zat-zat sisa dari metabolisme, termasuk asam urat dan urea. Akumulasi zat-zat ini dalam darah dapat menyebabkan pergeseran asam basa (Vermeulen and Vervloet, 2023), yang (Szlagor et al, 2023). Ginjal yang tidak berfungsi dengan baik tidak dapat membuang kelebihan cairan dari tubuh dengan efisien.…”
Section: B Pembahasanunclassified